GENERAL GEOLOGY OF KAMPUNG GUNONG SEMANGGOL, KAMUNTING, TAIPING WITH EMPHASIS ON RESERVOIR QUALITY ON TURBIDITE FACIES - BIN ZAINAL MALEK, MUHAMMAD SYAFIQ (Universiti Teknologi PETRONAS, 2014)
Semanggol Formation is divided into three separate sections (Northern, Central and Southern). It was found that many research have been done for the northern and central sections which are located in the Kedah state and only a few was done on the southern part (Perak state). The exposed Semanggol Formation for the south section is found in Gunung Semanggol which is located 13 km from Taiping. From this statement, further research must be done to increase geological information of this area (southern section). This research will be focused on the Western part of Gunung Semanggol’s North section and will emphasise on the depositional environment within the transect area. The targeted research area is located on the North West of the Perak state (Taiping) and is known to be formed from the Early Permian to Late Triassic. The lithology recorded from previous research indicates the presence of Sandstones, Conglomerate and Chert. The oldest known lithology in this formation is chert, followed by sandstone and the youngest is conglomerate. The formation is said to be younging towards the Northeast which has a lot of conglomerate which is found towards that direction. Structures found in Semanggol are of tight folds and consist of a series of asymmetrical folds having north-south trend. All information gathered are used to make the Geological Map of the transect area. At the same time, the generation of the cross section can be carried out. The generated map and cross section will show the lithological distribution (rock types and transect elevation) of the chosen area and further analysis will help in determining the depositional environment of the area. Correlation between field data and lab analysis (thin section and poroperm) will help in classifying the type of depositional environment and its contribution towards reservoir quality. Petrography works from the Thin Section will provide details on texture and grain size of the rocks and also the origin of the rock itself. Finally, the depositional environment can be modeled based on the features and data obtained from the lab analysis.